2007
DOI: 10.1002/jnr.21524
|View full text |Cite
|
Sign up to set email alerts
|

The peroxisome proliferator‐activated receptor‐γ agonist 1,1‐bis(3′‐indolyl)‐1‐(p‐trifluoromethylphenyl)methane suppresses manganese‐induced production of nitric oxide in astrocytes and inhibits apoptosis in cocultured PC12 cells

Abstract: Reactive astrogliosis is a prominent neuropathologic feature of manganism, a neurodegenerative disorder caused by excessive accumulation of manganese (Mn) in the basal ganglia. Activation of astrocytes has been linked to neuronal injury in manganism resulting from overproduction of inflammatory mediators, including tumor necrosis factor-alpha (TNFalpha), interferon-gamma (IFNgamma), interleukin-1beta (IL-1beta), and nitric oxide (NO), but the signaling mechanisms by which Mn regulates these factors remain poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Mn also strongly potentiates NO production in cytokine-stimulated astrocytes, leading to apoptosis in co-cultured neurons Spranger et al 1998;Tjalkens et al 2008). This observation is supported by studies demonstrating increased expression of NOS2 in activated astrocytes surrounding degenerating neurons in the striatum and globus pallidus of Mn-treated mice .…”
Section: Inflammatory Activation Of Gliamentioning
confidence: 99%
“…Mn also strongly potentiates NO production in cytokine-stimulated astrocytes, leading to apoptosis in co-cultured neurons Spranger et al 1998;Tjalkens et al 2008). This observation is supported by studies demonstrating increased expression of NOS2 in activated astrocytes surrounding degenerating neurons in the striatum and globus pallidus of Mn-treated mice .…”
Section: Inflammatory Activation Of Gliamentioning
confidence: 99%
“…Recently, it has been suggested that PPARγ agonists, including RSG, 1,1-bis(3′-indolyl)-1-(p-trifluoromethylphenyl)methane and pioglitazone, regulate inflammatory processes in the CNS and have neuroprotective effects against neurological and neurodegenerative disorders [17][18][19][20][21][22][23][24]. There are many reports on neuroprotective effects against ischemic damage using various drugs or materials [25][26][27][28].…”
Section: Introductionmentioning
confidence: 98%
“…The selected C-DIM compounds examined in this model, particularly C-DIM5 and 12, had excellent pharmacokinetic behavior after oral administration and were effective at inhibiting progressive loss of dopamine neurons in a postlesioning model of PD. In previous in vitro studies with two other C-DIM analogs in this series, 1,1-bis(39-indolyl)-1-(p-trifluoromethylphenyl)methane (C-DIM1) and 1,1-bis(39-indolyl)-1-(p-t-butylphenyl)methane (C-DIM4), we reported that these compounds suppressed activation of NF-kB in mixed glial cultures exposed to inflammatory stimuli that prevented expression of inducible nitric oxide synthase (NOS2) and protected cocultured neurons from apoptosis (Tjalkens et al, 2008;Carbone et al, 2009). The mechanism underlying this anti-inflammatory activity in glia involved stabilization of nuclear corepressor proteins that prevented DNA binding of NF-kB at cis elements in the Nos2 promoter.…”
Section: Tablementioning
confidence: 99%
“…The anti-inflammatory and neuroprotective efficacy of C-DIM compounds in neural cells was demonstrated by the capacity of selected para-phenyl-substituted analogs in this series to inhibit NF-kB-dependent expression of NOS2 in astrocytes and subsequent neuronal injury after inflammatory stimulation with cytokines and neurotoxins (Tjalkens et al, 2008;Carbone et al, 2009). On the basis of these in vitro findings, we generated pharmacokinetic data for each of the C-DIM compounds to determine their potential neuroprotective use in vivo.…”
Section: Introductionmentioning
confidence: 99%